Disentangling the Effects of Fair Trade on the Quality of Malian Cotton - Gaëlle Balineau (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
The increasing importance of premium segments and the proliferation of private labels and certification schemes raise skepticism about the ability of Fair Trade (FT) to help smallholders compete in high value-added markets. Based on a panel dataset collected in Mali in 2008, this paper contributes to the debate by estimating the impact of FT on the quality of Malian cotton. Controlling forselection bias and for a potential increase in quality prior to FT certification, results show a significant impact of FT on the quality of cotton produced by both certified and geographically close non-certified growers via spillover effects.
Keywords: P45; O13; O24; J54; 330